Recognition More Than Friendship: The Bicentennial of US-Brazil Relations, 1824–2024 - Andre Pagliarini (Latin American Research Review)
Marking the bicentennial of US-Brazil relations, this article assesses the fraught inception of the bilateral relationship and where it stands today. The United States, fueled by the ideals of its revolution, viewed itself in the nineteenth century as a beacon of democratic principles beset by powerful European discontents. Brazil’s position as an independent nation with deep ties to Portugal bred suspicion. The promulgation of Brazil’s 1824 Constitution offered a modicum of common ground, creating space for a political rapprochement culminating in formal recognition. The relationship thereafter was proper but distant. Brazil today is not a rival of the United States, but some worry that it has not done enough to distance itself from Washington’s antagonists. Indeed, while friendship and commonality have been common bywords of leaders in both nations, suspicion and ambivalence have been ever-present. If anything, the surprise is that both countries remain as close as they are today.